Hardware and software: verification and testing 6th International Haifa Verification Conference, HVC 2010, Haifa, Israel, October 4-7, 2010: revised selected papers - International Haifa Verification Conference 2010 Haifa, Israel); Barner, Sharon (Heidelberg New York Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Haifa Verification Conference, HVC 2010, held in Haifa, Israel in October 2010. The 10 revised full papers presented together with 7 invited papers were carefully reviewed and selected from 30 submissions. The papers address all current issues, challenges and future directions of verification for hardware, software, and hybrid systems and have a research focus on hybrid methods and the migration of methods and ideas between hardware and software, static and dynamic analysis, pre- and post-silicon.
Electronic reproduction.
Keywords: Software architecture -- Congresses; Computer input-output equipment -- Congresses; Computer software -- Verification -- Congresses